Excursions, Reversals, and Secular Variation: Different Expressions of a Common Mechanism? - B. A. Buffett (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Fluctuations in the geomagnetic field occur over a broad range of timescales. Short‐period fluctuations are called secular variation, whereas excursions and reversals are viewed as anomalous transient events. An open question is whether distinct mechanisms are required to account for these different forms of variability. Clues are sought in trends b of the axial dipole moment from six time‐dependent geomagnetic field models. Variability in b has a well‐defined dependence on the time interval (or window) for the trend. The variance of b reveals a simple relationship to trends during excursions and reversals. This connection hints at a link between reversals, excursions and secular variation. Stochastic models exhibit a similar behavior in response to random fluctuations in dipole generation. We find that excursions, reversals and secular variation can be distinguished on the basis of trend durations rather than differences in the underlying physical process. While this analysis does not rule out distinct physical mechanisms, the paleomagnetic observations suggest that such distinctions are not required.